2007
DOI: 10.1038/ng2072
|View full text |Cite
|
Sign up to set email alerts
|

Loss of GLIS2 causes nephronophthisis in humans and mice by increased apoptosis and fibrosis

Abstract: Nephronophthisis (NPHP), an autosomal recessive kidney disease, is the most frequent genetic cause of end-stage renal failure in the first three decades of life. Positional cloning of the six known NPHP genes has linked its pathogenesis to primary cilia function. Here we identify mutation of GLIS2 as causing an NPHP-like phenotype in humans and mice, using positional cloning and mouse transgenics, respectively. Kidneys of Glis2 mutant mice show severe renal atrophy and fibrosis starting at 8 weeks of age. Diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
258
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(270 citation statements)
references
References 28 publications
7
258
2
3
Order By: Relevance
“…45 We crossed these mice to kidney tubule cellspecific KspCad-Cre mice that had been successfully used to knock out other ciliary proteins, such as Kif3A, 35 which also cause early embryonic lethality when knocked out globally. 46,47 The phenotype in our Cdc42 kidney-specific knockout mice, especially the multiple small cysts, increased cell proliferation, increased apoptosis, and increased fibrosis, is more consistent with a nephronophthisis model 40 than ADPKD, in which greatly enlarged cystic kidneys are seen. 2 Although less common than ADPKD, nephronophthisis, a group of autosomal recessive disorders, is the most frequent genetic cause of ESRD up to the third decade of life.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…45 We crossed these mice to kidney tubule cellspecific KspCad-Cre mice that had been successfully used to knock out other ciliary proteins, such as Kif3A, 35 which also cause early embryonic lethality when knocked out globally. 46,47 The phenotype in our Cdc42 kidney-specific knockout mice, especially the multiple small cysts, increased cell proliferation, increased apoptosis, and increased fibrosis, is more consistent with a nephronophthisis model 40 than ADPKD, in which greatly enlarged cystic kidneys are seen. 2 Although less common than ADPKD, nephronophthisis, a group of autosomal recessive disorders, is the most frequent genetic cause of ESRD up to the third decade of life.…”
Section: Discussionsupporting
confidence: 67%
“…40 To investigate this, we first examined bromodeoxyuridine (BrdU) incorporation, a marker of active cell division, in sections of kidneys from the Cdc42 kidney-specific knockout mice and wild-type littermate controls, and found it to be significantly increased in the Cdc42 conditional knockout kidneys ( Figure 8, A-C). We next examined apoptosis, using terminal deoxynucleotidyl transferase-mediated digoxigenin-deoxyuridine nick-end labeling (TUNEL) staining, and found it to be increased as well in Cdc42 kidney-specific knockout mice (Figure 8, D-F).…”
Section: Ciliogenesis Is Inhibited In Cdc42 Kidney-specific Knockout mentioning
confidence: 99%
“…210 Major epithelial mechanisms contributing to chronic tubulointerstitial fibrosis are G2/M cell cycle arrest, 181 cellular apoptosis, 211 and EMT-forming fibroblasts; 147,151 all three processes are modulated by the transcriptional repressor GLIS2. 212 EMT is a fundamental process to create cells that will move, 155 a modification in lineage maturation that disturbs the state of nuclear diapause in epithelial and endothelial cells. 59, 213 Although not all agree, 54,159,214,215 11 studies confirm these transitions to fibroblasts in a variety of lineage-tracing experiments from different tissues, including kidney, 50,59,60,165 intestine, 216 liver, 217 heart, 166 lung, 218 -220 and endothelium 50,166,221 using 10 different cell fate reporter constructs.…”
Section: Fibroblastsmentioning
confidence: 99%
“…226 Glis2 mutations producing autosomal recessive NPHP7, a rare form of nephronophthisis, may be the first suggestive evidence of spontaneous or derepressed EMT causing renal fibrosis in humans. 212,227 EMT induces a variety of intermediate cell phenotypes, not all of which complete their transition to fibroblasts. 147,225 This intermediacy and its reversibility may depend on the variable persistence of endogenous perturbagens: hypoxia, 165,228 -230 TGF␤, 231 EGF, 231,232 PTH-RP, 233 and plasmin 97 all induce EMT, as does activation of ILK 49 or RAGE.…”
Section: Fibroblastsmentioning
confidence: 99%
“…14 In the second, loss of the transcription factor, Glis2, a member of the Kruppel-like C2H2 zinc finger protein subfamily, which includes the GLI proteins, resulted in nephronophthisis in humans and mice. 15 Expression profiling of Glis2 2/2 kidneys revealed an upregulation of Gli1, a direct target of the pathway, suggesting upregulated Hh signaling. Finally, a study examining the effects of corticosteroid overexposure on metanephric development found that adding hydrocortisone to a metanephros organ culture unexpectedly caused renal cysts as well as upregulated Ihh transcripts.…”
mentioning
confidence: 98%